You got served - Morton, Marcus; Weathersby, Cassius Vernon; Pollina, Billy; Stokes, Christopher B.; Houston, Marques, 1981-; Grandberry, Omari, 1984-; Houston, Jarell, 1985-; Thornton, DeMario, 1985-; Lil Fizz.; Freeman, Jennifer, 1985-; Lil' Kim.; Taliferrio, Michael; et al. (Culver City, Calif. : Columbia TriStar Home Entertainment, 2004)
At Mr. Rad's Warehouse, the best hip-hop crews in Los Angeles compete for money and respect. But a crew from the suburbs moves in and crashes the party, stealing their dancers, and their moves. Elgin and David are street dancers who will have to pull together in order to believe in themselves, their crew, and in their dreams if they are to represent the streets and win the challenge and the money that is up for grabs.
Originally released as a motion picture in 2003.
Special features: video and audio commentary; director and cast commentary; serve it up: the making-of 'You got served'; "Badaboom" music video by B2K; battle of the beat featurette; dance breakdown; multi-angle feature; dance breakdown intro by Billy Pollina.
Director of photography, David Hennings ; editor, Earl Watson ; music, Tyler Bates ; costume designer, Ca-Trece Mas'sey ; production designer, Maxine Shepard ; choreographers, Dave Scott, Shane Sparks.
Marques Houston, Omari Grandberry, Jarell Houston, DeMario Thornton, Dreux Frederic, Jennifer Freeman, Lil' Kim, Michael "Bear" Taliferrio, Alani "La La" Vasquez, Steve Harvey.
MPAA rating: PG-13; for thematic elements and sexual references.
DVD, Region 1, widescreen presentation; Dolby Digital, DTS.
Keywords: Hip-hop -- Drama; Competition (Psychology) in adolescence -- Drama; Video recordings for the hearing impaired; Feature films